2000
DOI: 10.1063/1.1314877
|View full text |Cite
|
Sign up to set email alerts
|

X-ray diffraction analysis of the defect structure in epitaxial GaN

Abstract: High-resolution x-ray diffraction has been used to analyze the type and density of threading dislocations in (001)-oriented GaN epitaxial layers. For this, (00l) and (hkl) Bragg reflections with h or k nonzero were studied, the latter one measured in skew symmetric diffraction geometry. The defect analysis was applied to a variety of GaN layers grown by molecular-beam epitaxy under very different conditions. The outcome is a fundamental correlation between the densities of edge- and screw-type dislocations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
195
1
3

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 324 publications
(216 citation statements)
references
References 20 publications
17
195
1
3
Order By: Relevance
“…However, we have also found that the relative intensity of yellow luminescence exhibits a random fluctuation when the DCXRD FWHM at the (002) plane increases (not shown here). It has been reported that the GaN samples with narrower DCXRD FWHM at the (002) plane have lower screw dislocation densities, while the GaN samples with narrower FWHM at the (102) plane have lower edge dislocation densities (Heying et al, 1996;Heinke et al, 2000). Therefore, the above-mentioned results suggest that the intensity of the yellow luminescence band in n-type GaN is not influenced by the density of screw dislocations, but is strongly related to the edge dislocations.…”
Section: Yellow Luminescence and Related Defects In Gan Materialsmentioning
confidence: 56%
See 1 more Smart Citation
“…However, we have also found that the relative intensity of yellow luminescence exhibits a random fluctuation when the DCXRD FWHM at the (002) plane increases (not shown here). It has been reported that the GaN samples with narrower DCXRD FWHM at the (002) plane have lower screw dislocation densities, while the GaN samples with narrower FWHM at the (102) plane have lower edge dislocation densities (Heying et al, 1996;Heinke et al, 2000). Therefore, the above-mentioned results suggest that the intensity of the yellow luminescence band in n-type GaN is not influenced by the density of screw dislocations, but is strongly related to the edge dislocations.…”
Section: Yellow Luminescence and Related Defects In Gan Materialsmentioning
confidence: 56%
“…As shown in Table 1, sample A has a narrower FWHM of x-ray rocking curve and a higher electron mobility, it seems that the longer annealing time of low-temperature AlN buffer layer tends to promote a lateral growth of GaN islands, and the quality of GaN epilayers is improved. It also suggests that the lateral growth of GaN islands is helpful to decrease the edge threading dislocations, since the FWHM of x-ray ω-scan rocking curve for (0002) and (10-12) planes represents indirectly the density of screw and edge threading dislocations (Heying et al, 1996;Heinke et al,2000).…”
Section: Gan Materials Growth Using the Two-step Methodsmentioning
confidence: 99%
“…(002) and asymmetrical (102) reflections present the information about the mixed threading dislocation density and pure edge dislocation density, respectively [7,8]. Figure 3(a) and 3(b) illustrate the variation tendency of the FWHM values of GaN (002) plane and (102) plane for the samples dependent on different deposition temperatures, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Ideal structural parameters for all the layers were taken from the papers [17,18]. Dislocation density measurements were performed like to those in works [19,20]. The thickness of individual layers in SL and its period were controlled using X-ray reflectivity and secondary neutral mass-spectrometry (SNMS).…”
Section: Methodsmentioning
confidence: 99%